Finite mathematics : for management, life, and social sciences - Harshbarger, Ronald J.; Reynolds, James J. (Lexington, Mass. : D.C. Heath, 1989)
This desirable goal is not always an easy one to realize with students whose primary interest is in an area other than mathematics.
1. Sets, linear equations, and functions -- 2. Matrices -- 3. Inequalities and linear programming -- 4. Mathematics of finance -- 5. Introduction to probability -- 6. Introduction to statistic -- 7. Game theory.
Includes index.
Keywords: MATHEMATICS; SOCIAL SCIENCES -- MATHEMATICS; BIOMATHEMATICS